The ability of an attaching and effacing pathogen to trigger localized actin assembly contributes to virulence by promoting mucosal attachment. (2nd June 2014) - Mallick, Emily M.; Garber, John J.; Vanguri, Vijay K.; Balasubramanian, Sowmya; Blood, Timothy; Clark, Stacie; Vingadassalom, Didier; Louissaint, Christopher; McCormick, Beth; Snapper, Scott B.; Leong, John M.
Summary Enterohaemorrhagic Escherichia coli (EHEC) colonizes the intestine and causes bloody diarrhoea and kidney failure by producing Shiga toxin. Upon binding intestinal cells, EHEC triggers a change in host cell shape, generating actin 'pedestals' beneath bound bacteria. To investigate the importance of pedestal formation to disease, we infected genetically engineered mice incapable of supporting pedestal formation by an EHEC‐like mouse pathogen, or wild type mice with a mutant of that pathogen incapable of generating pedestals. We found that pedestal formation promotes attachment of bacteria to the intestinal mucosa and vastly increases the severity of Shiga toxin‐mediated disease.